Β2-Adrenergic genotypes and risk of severe exacerbations in COPD: a prospective cohort study. Issue 10 (3rd September 2019) - Ingebrigtsen, Truls Sylvan; Vestbo, Jørgen; Rode, Line; Marott, Jacob Louis; Lange, Peter; Nordestgaard, Børge G
Abstract : Background: Individual susceptibility to exacerbations in chronic obstructive pulmonary disease (COPD) is likely influenced by genetic factors; however, most such variance is unexplained. We hypothesised that β2 -adrenergic receptor genotypes, Gly16Arg (rs1042713, c.46G>A) and Gln27Glu (rs1042714, c.79C>G) influence risk of severe exacerbations in COPD. Methods: Among 96 762 individuals in the Copenhagen General Population Study, we identified 5262 with COPD (forced expiratory volume in one second divided by forced vital capacity, FEV1 /FVC, below 0.7, FEV1 less than 80% of predicted value, age above 40 years and no asthma) who had genotyping performed. Severe exacerbations were defined as acute admissions due to COPD during 5 years of follow-up (mean 3.4 years). 923 individuals with COPD diagnosed similarly in the Copenhagen City Heart Study (CCHS) were used for replication analyses. Results: We recorded 461 severe exacerbations in 5262 subjects. The HRs for severe exacerbations were 1.62 (95% CI 1.30 to 2.03, p=0.00002) for 16Gly/Arg heterozygotes and 1.41 (1.04 to 1.91, p=0.03) for 16Arg homozygotes, compared with 16Gly homozygotes. HRs were 1.35 (1.03 to 1.76, p=0.03) for 27Gln/Glu heterozygotes and 1.49 (1.12 to 1.98, p=0.006) for 27Gln homozygotes, compared with 27Glu homozygotes. Similar trends were observed in the CCHS. Among 27Gln homozygotes only, HRs were 5.20 (1.81 to 14.9, p=0.002) for 16Gly/Arg heterozygotes and 4.03 (1.40 to 11.6, p=0.01) for 16Arg homozygotes, compared with 16Gly homozygotes. Conclusion: Common β2 -adrenergic receptor genotypes influence risk of severe exacerbations in COPD, potentially mainly by genetic influence of the 16Arg allele in rs1042713.